Capitalism and class in the Gulf Arab states - Hanieh, Adam (Palgrave Macmillan, 2011)
The six Arab states of the Gulf Cooperation Council (GCC) play an increasingly prominent role in the global economy and throughout the broader Middle East region. Accompanied by an extensive empirical analysis of all sectors of the GCC economy, the book argues that a new capitalist class, Khaleeji Capital, is forming in the Gulf--with profound implications for the Middle East as a whole.